PROBLEMS OF TEACHING ENGLISH GRAMMAR AND STRATEGIES TO SOLVE THEM - Ernazarova, Nigina (Журнал иностранных языков и лингвистики, 2023)
It has been a major growth point in the ELT (English Language Teaching) industry over the last ten years. Some people, though, refer to learning taking place while the focus is on other activities. For example, playing a card game that requires calling for cards may allow learn grammar. When talking about language skills, the four basic ones are: listening, speaking, reading and writing. However, other, more socially-based skills have been identified more recently such as summarizing, describing, narrating etc. In addition, more general learning skills such as study skills and knowing how one learns have been applied to language classrooms. The present work is aimed to find out certain problem and solutions in teaching English grammar.